The impact economic growth towards foreign direct investment in China / Abdul Rafiq Abdul Aziz - Abdul Aziz, Abdul Rafiq (Faculty of Business Management, 2017)
This study aims to examine the relationship and impact between the economic growth and foreign direct investment (FDI) in China and also, to determine the determinant factors of foreign direct investment that influence the economic growth in China. This study will use time series analysis and multiple regression models. This study will be conducted by using the quarterly data on foreign direct investment and economic growth in China that covering the periods of 1995 until 2016 which is 22 years. The data were collected from a particular database that is Data Stream and the information also is gathered from the previous journals and websites that are related with this study as a references. The researcher also used the EVIEWS (Econometric View) software from 8.0 version to examine and analysed the data in order to get the outcome of the research whether the variables is positively or negatively significant to each other. The dependent variable are FDI inwards which represent as foreign direct investment (FDI) while, the independent variable are selected macroeconomics variables which are the gross domestic product, import and exports that wil l represent as economic growth. The findings in this research shows that GDP have positive relationship with the FDI in China while imports and export have no significant relationship between FDI in China.